Identifying the issues leading to residents’ modifications in Bahraini subsidized housing units - Lafi, May Walid; Alkhalifa, Haifa Ebrahim; Jiwane, Anamika Vishal (Frontiers in Built Environment, 2023)
Residents' modifications in subsidized housing are a widespread phenomenon in Bahrain. Households begin to modify their allocated residential units as soon as they receive them, resulting in financial burdens and an aesthetic loss of the uniform physical appearance. This research aims to identify the issues leading to residents' modifications in Bahraini subsidized housing units. Literature indicates that this phenomenon is closely related to resident behaviors. Thus, the study presents a conceptual framework that examines the similarities and differences in residents' behaviors in subsidized housing. Accordingly, the study employed the qualitative approach and was conducted in two phases. The first phase investigated common resident behaviors through structured interviews with twelve experts involved in the modification process. The second phase used the case study strategy with three selected cases from the East Hidd housing project to examine the different behaviors related to residents' lifestyles. It included on-site observations, plan analysis, and structured interviews with family members using the AIO approach. The findings revealed general and specific issues that lead to residents' modifications in Bahraini subsidized housing units. On the one hand, the general issues represent common behaviors for most residents and are usually associated with the prior-occupancy stage. They include Bahraini residents' preference for simple modern designs, such as spacious living rooms and bedrooms, modern materials, large windows, and glazed sliding doors overlooking the courtyard; Bahraini residents' need for sustainable housing units that incorporate all three aspects of sustainability, particularly the socio-cultural, which is related to factors like privacy, hospitality, and the aesthetics and distinction of houses; and the damages resulting from the improper practices of the residents that mainly revolve around excluding the experts and involving the unqualified in the modifications process. On the other hand, the specific issues represent families' different behaviors and are usually associated with the post-occupancy stage. Those include Bahraini residents' need to modify their houses according to their varying lifestyles, evident in the guest room, the courtyard, and the interior divisions of the extended bedroom. Therefore, the study concludes that considering both issues when designing future projects contributes to reducing and streamlining the process of modifications.